A New Method of Bone Stromal Cell Characterization by Flow Cytometry. Issue 3 (29th March 2022) - Patel, Chirayu; Shi, Lihong; Whitesides, John F.; Foster, Brittni M.; Fajardo, Roberto J.; Quillen, Ellen E.; Kerr, Bethany A.
Abstract: The bone microenvironment cellular composition plays an essential role in bone health and is disrupted in bone pathologies, such as osteoporosis, osteoarthritis, and cancer. Flow cytometry protocols for hematopoietic stem cell lineages are well defined and well established. Additionally, a consensus for mesenchymal stem cell flow markers has been developed. However, flow cytometry markers for bone‐residing cells—osteoblasts, osteoclasts, and osteocytes—have not been proposed. Here, we describe a novel partial digestion method to separate these cells from the bone matrix and present new markers for enumerating these cells by flow cytometry. We optimized bone digestion and analyzed markers across murine, nonhuman primate, and human bone. The isolation and staining protocols can be used with either cell sorting or flow cytometry. Our method allows for the enumeration and collection of hematopoietic and mesenchymal lineage cells in the bone microenvironment combined with bone‐residing stromal cells. Thus, we have established a multi‐fluorochrome bone marrow cell‐typing methodology. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Partial digestion for murine long bone stromal cell isolation Alternate Protocol 1 : Partial digestion for primate vertebrae stromal cell isolation Alternate Protocol 2 : Murine vertebrae crushing for bone stromal cell isolation Basic Protocol 2 : Staining of bone stromal cells Support Protocol 1 : Fluorescence minus one control, isotype control, and antibody titration Basic Protocol 3 : Cell sorting of bone stromal cells Alternate Protocol 3 : Flow cytometry analysis of bone stromal cells Support Protocol 2 : Preparing compensation beads